Persepsi Audiens tentang Kompetensi Public Speaking Petugas Badan Narkotika Nasional Provinsi (BNNP) Jawa Tengah dalam Kegiatan Sosialisasi Pencegahan Pemberantasan Penyalahgunaan Dan Peredaran Gelap Narkoba (P4GN) di Kalangan Peserta Sosialisasi - Ribka Minatisari Sekeon; M Yulianto; Agus Naryoso; Joyo NS Gono (Interaksi Online, 2015)
Prevention and Eradication of Illicit Drug Abuse dissemination activities undertakenby the Central Java BNNP basically aims to sensitize the public about the dangers of drug use. In this socialization certainly has a specific purpose and contains a lot of values andthings that would be submitted or implanted in the minds of the public. This study aimed to determine the audience's perception of the competence of public speaking officer in theCentral Java BNNP Prevention and Eradication of Illicit Drug Abuse socialization among participants sozialization. It is assessed by the audience became one of which was consideredideal or not by the audience. The theory used is the Communication Competency whichbasically refers to the speaker's ability to communicate effectively, means of communicationwill affect the audience, if the speaker has the competence: knowledge of the content of the message of public communication, motivation expressed communicator, non-verbal abilityand technical ability. Competencies that make the speaker assessed by the audience to raisethe audience's perception of the speaker who is considered to have a good competence as a speaker or not.This type of research is a descriptive study using a quantitative approach with surveyresearch methods. The sampling technique using nonprobability sampling with saturatedsample method. This study uses positivism paradigm. Data collection tool was a questionnaire with the use of questionnaires to respondents. Analysis of data usingdescriptive statistics to classify the answer in the form of mono table.Broadly speaking, the results of this study stated that the Central Java BNNP Officerscompetent in doing public speaking competence. However, there are still some shortcomingsof Officers BNNP Central Java, it is advisable to further establish a close relationship withthe audience, to adapt the communication with the audience, and the corresponding timemanagement.